Urine Metabolite Risk Factors of DJ Stent’s Biofilm Formation in Patients with Urinary Tract Stones - Besut Daryanto; Muhammad Miftahul Firdaus (Brawijaya Journal of Urology, 2020)
Introduction: Since first introduced by Finney and Hepperlen in 1978, the Double-J "DJ" Stent has become a routine armament that every Urologist uses everyday. Over time, there have been developments and improvements in both designs and materials, in order to improve the efficacy of the stents themselves. The use of the DJ Stent can not be separated from the morbidity or complications that might occur, including discomfort arising from the insertion of stents, forgotten to remove, urinary tract infections, biofilm formation, even encrustation of the stent. This research aims to know the correlation between the urine metabolites condition and urinary tract infection in the formation of biofilm and encrustation in patients with urinary tract stones at Saiful Anwar General Hospital, Malang. Method: This is a cohort study using chi-square analysis and relative risk calculation. The datas were obtained from patients at Saiful Anwar General Hospital from March 2016 until December 2017. The examination includes urine metabolites, urinalysis, and urine culture prior to the insertion of DJ Stent, at polyclinic, and before the removal of DJ Stent. After the DJ Stent was removed, we evaluate if there was an encrustation on the DJ Stent or not and biofilm using congo agar plate. The subjects in this research was patient with urinary tract stone and patient without urinary tract stone as control group. Result: There were 60 patients with urinary track stones, as well as 60 patients without a urinary track stone as a control. We found that high level of uric acid prior to removal of DJ Stent and during polyclinic control, and also high level of magnesium urine before DJ Stent removal were five times higher to form biofilm in patients with urinary tract stones. The presence of urinary tract infections when the subject control at polyclinic and before DJ Stent removal, and the presence of bacteria in urine before the insertion of DJ Stent in patients with urinary tract stones is significantly have five times higher risk to form encrustation on the DJ stent. Patients without urinary tract stone have four times higher risk in the formation of encrustation with abnormal level of magnesium that found before the removal of DJ Stent. Delayed in DJ Stent removal in patients without urinary track stone were significantly have ten times higher risk in biofilm formation and six times higher risk in the formation of encrustation in patients with urinary tract stones. Conclusions: There is a relationship between the condition of urine metabolites and urinary tract infections with biofilm formation and DJ Stent's encrustation in patients with urinary tract stones.